2009
DOI: 10.1093/brain/awp306
|View full text |Cite
|
Sign up to set email alerts
|

Atypical neural self-representation in autism

Abstract: The 'self' is a complex multidimensional construct deeply embedded and in many ways defined by our relations with the social world. Individuals with autism are impaired in both self-referential and other-referential social cognitive processing. Atypical neural representation of the self may be a key to understanding the nature of such impairments. Using functional magnetic resonance imaging we scanned adult males with an autism spectrum condition and age and IQ-matched neurotypical males while they made reflec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
246
0
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 326 publications
(268 citation statements)
references
References 115 publications
18
246
0
4
Order By: Relevance
“…Previous studies have shown that people with autism struggle when making selfreferential judgements (Frith and de Vignemont 2005;Lombardo et al 2010), which has been related to an inability to properly distinguish between the self and others. The ability to perform the egocentric task required the participant to use the self as a reference point for performing a spatial transformation.…”
Section: Egocentric Transformations Taskmentioning
confidence: 99%
“…Previous studies have shown that people with autism struggle when making selfreferential judgements (Frith and de Vignemont 2005;Lombardo et al 2010), which has been related to an inability to properly distinguish between the self and others. The ability to perform the egocentric task required the participant to use the self as a reference point for performing a spatial transformation.…”
Section: Egocentric Transformations Taskmentioning
confidence: 99%
“…Benoit, Gilbert, Volle, & Burgess, 2010;Northoff et al, 2006;Sugiura et al, 2012) and is thought to contribute to atypical selfrepresentations in a variety of groups (e.g. see Lombardo et al, 2010;Wang, Metzak, & Woodward, 2011). While these studies tend to implicate more ventral aspects of the mPFC to selfrepresentations, prior functional neuroimaging work has indicated that the dorsal mPFC plays an important role in processing self-other discrepancy (Tamir & Mitchell, 2010).…”
Section: Differences Between Mirror-touch Synaesthetes and Controlsmentioning
confidence: 99%
“…There is accumulating evidence of these regions' involvement in the control of self-other representations (e.g. Brass et al, 2009;Lombardo et al, 2010;Santiesteban et al, 2012;Spengler et al, 2010;van Overwalle, 2009). For example, Santiesteban et al, (2012) found that excitatory stimulation of TPJ showed enhanced ability to distinguish between self and other during the imitation inhibition and visual perspective taking tasks.…”
Section: Discussionmentioning
confidence: 99%